Directed Self-Assembly of Block Copolymer for Bit Patterned Media with Areal Density of 1.5 Teradot/Inch2 and Beyond. (22nd December 2013) - Yang, XiaoMin; Xiao, Shuaigang; Hsu, Yautzong; Feldbaum, Michael; Lee, Kim; Kuo, David
Abstract : Directed self-assembly (DSA) of block copolymer (BCP) holds great promise for many applications in nanolithography, including the next generation magnetic recording. In this work, directed self-assembly of block copolymer technique has been combined with rotary stage electron beam mastering to fabricate a circular full track nanoimprint template for bit patterned media (BPM) fabrication. In order to meet specific requirements in pattern structure and format between the data and the servo zone in a servo-integrated template, three types of lithographically defined prepatterns, (1) two-dimensional chemical pre-pattern, (2) two-dimensional low-topographic pre-pattern, and (3) one-dimensional high-topographic pre-pattern, have been explored for DSA process with two types of commercially available BCP thin film materials: cylinder-forming poly(styrene- b -methyl methacrylate) (PS- b -PMMA) and sphere-forming poly(styrene- b -dimethylsiloxane) (PS- b -PDMS). All guided BCP patterns exhibit highly ordered hexagonal close-packed (hcp) structures with high pattern quality. Using these BCP patterns, two polarities of dots-array templates (hole-tone and pillar-tone) with integrated servo patterns have been fabricated on a fused silica substrate at a density greater than 1.0 Td/in 2 . Furthermore, the fabricated master template has been used for UV-cure nanoimprint lithography process development on 2.5 inch disk size media. Good pattern uniformity in imprint resist has been achieved over an entire 2.4 mm wide band area. The imprint resist patterns have been further transferred into underlying CoCrPt media by ion beam etching. Evidently, for the first time, the patterned CoCrPt alloy dots (hcp pattern) have successfully been demonstrated at a high density of  1.5 Td/in 2 (pitch = 22.3  nm) for a guided media ( H c ≅ 7   kOe ) and 3.2 Td/in 2 (pitch = 15.2  nm) for an unguided media ( H c ≅ 5   kOe ) .